Project life cycle in open source software development / Deelailla Pakhalan - Pakhalan, Deelailla (Faculty of Computer and Mathematical Sciences, 2005)
The usage of open source is getting wider nowadays. Day by day the number of open source software project getting higher. Successfuiness of open source project is one of the reasons why open source software is getting popular. When we talk about successfuiness of a project, we will turn to the project management of the software development. Project management is a crucial part in software development to ensure the project success. As we know, the environment of the open source is different with the environment of the close source, where in the open source environment, the community or the project team is physically distributed. Therefore, the project management of both close and open source also different. The research is a qualitative study, aiming to develop new model of project life cycle in open source software development, identify project management's attributes, and the project time management in the open source software development. The main research method is interviews; that are carried out to some coordinators and contributors of the open source development. The analysis of the findings shows that attributes that involved in open source software are purpose, ownership, resources, roles, risk and assumption, interdependent task regardless timeline, organizational change and operating in an environment larger than the project itself. Project time management is depends on the project itself but for most of the open source project, there will always be six months to complete a new release. The proposed model is divided into five phases, where each one of these phases contains a set of associated activities. As a conclusion, the proposed model and the analysis perhaps could contribute to meet market expectations nowadays.